Access to RNA Encapsidated in the Nucleocapsid of Vesicular Stomatitis Virus - Green, Todd J. (American Society for Microbiology (ASM), 2011)
The genomic RNA of negative-strand RNA viruses, such as vesicular stomatitis virus (VSV), is completely enwrapped by the nucleocapsid protein (N) in every stage of virus infection. During viral transcription/replication, however, the genomic RNA in the nucleocapsid must be accessible by the virus-encoded RNA-dependent RNA polymerase in order to serve as the template for RNA synthesis. With the VSV nucleocapsid and a nucleocapsid-like particle (NLP) produced in Escherichia coli, we have found that the RNA in the VSV nucleocapsid can be removed by RNase A, in contrast to what was previously reported. Removal of the RNA did not disrupt the assembly of the N protein, resulting in an empty capsid. Polyribonucleotides were reencapsidated into the empty NLP, and the crystal structures were determined. The crystal structures revealed variable degrees of association of the N protein with a specific RNA sequence.